MODELING THE PROCESS OF PROTEIN SYNTHESIS IN THE DUCKWEED - Sergeeva I.Y.; Al Kassab A.A. (Техника и технология пищевых производств, 2017)
Currently, duckweed is considered to be a cheap and effective way to treat wastewater from farm bioreactors. In addition to the environmental benefits, the productive duckweed biomass of the produced during wastewater treatment contains a high content of nutrients, especially protein that positions it as an additional ingredient in the feed of farm animals, poultry and fish. The influence of cultivation conditions of Lemna minor on protein synthesis taking into account the variation of nutrient concentration in wastewater are studied. The cultivation system combining an anaerobic bioreactor as well as the system of growing duckweed is used. Specific growth rate of duckweed, which was 2.68; 3.85 and 4.61 g/(m2/day) of the substrate concentration of 20, 40 and 60% respectively, is determined. The maximum growth density has been obtained (g/m2): 67.4 for 20% of the substrate on the 30th day;63.0 for 40% of the substrate and 66.0 for 60% of the substrate on the 27th day of cultivation. The dynamics of total Kjeldahl nitrogen content in duckweed has been studied. The greatest content of total nitrogen in duckweed grown on nutrient medium with 20% substrate concentration is observed on the 15th day with a maximum accumulation rate of 0.16 g/m2/day. On the 21st day ofcultivation in a substrate with 40% concentration a maximum total nitrogen is recorded at a storage rate of 0.20 g/m2/day; with a 60% wastewater content - at a rate of 0.24 g/m2/day. The dynamics of protein synthesis in the duckweed has been studied. In the course of the experiment it has been found that on the 16th day of cultivation the maximum percentage of protein content in the duckweed for 20% substrate is observed as 27.62%, while for 40% it is 28.13% and for 60% - of 29.14% to the 19-th day of cultivation. Based on the results of the studies, a mathematical model has been calculated, which can be considered adequate, and can be used to predict the protein content of the duckweed species Lemna minor depending on the nutrient concentration in the substrate and the duration of cultivation.